Cervical Radiculopathy Caused by a Vertebral Artery Loop: Is a Focused Fluoroscopic‐Guided Cervical Epidural Steroid Injection a Possible Treatment Modality?. Issue 7 (7th May 2020) - Croci, Davide Marco; Koetsier, Eva; Maino, Paolo; Reinert, Michael; Robert, Thomas; Scarone, Pietro
Abstract: We describe a case of a patient suffering with cervical radiculopathy due to vertebral artery loop with nerve root compression, treated with an epidural steroid injection. A 37‐year‐old man presented with a 2‐year history of right‐sided radicular pain along the C7 dermatome. Imaging showed a right‐sided loop of the vertebral artery at the V1–V2 transition with contact on the C7 nerve root. The pain was resistant to conservative treatment, and the decision was made to perform a focused fluoroscopy‐guided translaminar epidural steroid injection near the C7 nerve root. The procedure was uneventful, and the symptoms resolved completely after the procedure. Targeted epidural steroid injection might be a useful and safe diagnostic and therapeutic approach in patients affected by cervical radiculopathy due to a VA loop. To our knowledge, this is the first case of a VA loop associated with cervical radiculopathy treated with this technique.